Açaí (Euterpe oleracea Mart) Consumption and Prevention of Chronic Diseases: Is There an Association? A Preliminary Study. (1st June 2020) - Silva, Dulcelena Ferreira; Custódio Neto da Silva, Marcos Antonio; Rodrigues, Gabrielle Meirelles; Vidal, Flávia Castello Branco; Barbosa, Maria do Carmo Lacerda; Oliveira Brito, Luciane Maria; Bezerra, Geusa Felipa de Barros; Muniz Filho, Walbert Edson; Borges, Kátia Regina Assunção; Rosa, Ivone Garros; de Carvalho, João Ernesto; Soares Brandão Nascimento, Maria do Desterro
Abstract : Background . Flavonoids from a variety of fruits, including açaí, have beneficial antioxidant activity in several diseases, including cancer. Breast cancer is the second most prevalent cancer among Brazilian women. Studies have shown the action of flavonoids on neoplastic cells, as well as on diabetes and neurodegenerative and cardiovascular diseases. Objective . To analyze the relationship between the consumption of açaí and the presence of chronic diseases in women residing in the rural area of São Luís, Maranhão. Methods . A convenience sample of 150 women residing in the Maracanã neighborhood in São Luís, Maranhão, was used; the collected data included sociodemographic characteristics, habits, sexual and reproductive history, consumption of açaí, and history of cancer and other chronic diseases. The sample was divided into women who consumed açaí at least once a week (cases) and women who did not consume açaí (controls). Statistical analysis was performed to assess the relationships between those variables and the consumption of açaí. Results . A total of 141 women (94%) consumed açaí. Among these, 79.3% were aged between 20 and 50 years, 78.67% were farmers or housewives, 64.67% were Pardo (mixed race), 76.67% were nonsmokers, 70% were not receiving hormonal therapy, 40.67% had already undergone mammography, 28% had already undergone breast ultrasound, and 27.33% had a family history of cancer, with breast cancer being the second most prevalent cancer. There was a higher prevalence of hypertension among women who did not consume açaí than that among those who did; however, previous cancer, family history of cancer, heart disease, and diabetes were more prevalent among the consumers of açaí. There were no statistically significant relationships. Conclusion . Flavonoids are known to have a beneficial effect on some types of neoplastic cells and other diseases; therefore, larger studies are necessary to better evaluate the beneficial effects of consuming foods containing flavonoids on these diseases.